A New Route for the Enzymeless Trace Level Detection of Creatinine Based on Reduced Graphene Oxide/Silver Nanocomposite Biosensor. Issue 2 (14th September 2016) - Viswanath, K. Balaji; Devasenathipathy, Rajkumar; Wang, Sea‐Fue; Vasantha, V. S.
Abstract: Renal insufficiencies and muscle diseases can be easily identified from the concentration of creatinine in blood and urine. Although various chemical sensors have been developed to detect creatinine, selectivity and robustness of chemical sensors are the main obstacles for many researchers. To overcome these difficulties, finding a suitable chemical biosensor with long‐term stability, low cost, high sensitivity and selectivity for the detection of creatinine is immensely desirable. Herein, we have developed a novel enzymeless creatinine biosensor for the trace level detection of creatinine using reduced graphene oxide (RGO)/ silver nanoparticles (AgNPs) which was prepared by simple one step electrochemical potentiodyanamic method. The anodic peak current of AgNPs gradually decreased when the concentration of creatinine was increased. Based on the decrease of anodic peak current, we have introduced a new platform for the detection of creatinine. The adsorption of creatinine on AgNPs was confirmed by various techniques. The newly proposed biosensor exhibited a very low detection limit of 0.743 pM with linear range from 10 pM to 120 pM. The demonstrated sensor can detect creatinine even in the presence of other interfering biomolecules such as glucose, ascorbic acid, uric acid, urea and creatine. Abstract :